Entropy in the city of Zaragoza. cartography to analyze social diversity and intraurban residential segregation.: Map - Postigo Vidal, Raúl; Valdivielso Pardos, Sergio; Pueyo Campos, Ángel (Geographicalia, 2023)
The measurement of social diversity and residential segregation has sparked notable interest in academic, technical, and particularly urban planning circles. However, the reliability of cartographic instruments has been conditioned by the methods and techniques of geodemographic analysis and also by the availability of disaggregated data. This article proposes innovations in the cartographic representation procedure of the entropy index (H2), a multigroup segregation index that enables quantitative and spatial analysis of the residential composition of large groups of foreign population at the block level. The map reveals intraurban contrasts in residential segregation in the city of Zaragoza, employing a multidimensional cartographic representation that combines multiple visual variables, real variables, and instrumental methods to try to understand the complexity of socio-spatial relationships at the intraurban scale.